PENDIDIKAN PLURALISME MELALUI KURIKULUM PENDIDIKAN AGAMA ISLAM BERBASIS KEMAJEMUKAN - ., Mutakallim (Universitas Islam Negeri Alauddin Makassar, 2018)
Experts and religious leaders have tried everything in order to create an intimate and harmonious relationship between religious people in this famous, very pluralistic country of Indonesia. Through writings both books, magazines, journals and even through seminars and pulpits of sermons always suggest the importance of cooperation and dialogue between religious groups. Although it seems, their suggestions have not had such an exciting effect. To gain success for the realization of the noble goal of lasting peace and brotherhood among people who in reality have different religions and faiths, it is necessary to have the courage to invite them to make changes in the field of education, especially through a diversity-based curriculum. Because, through a curriculum like this, it is possible to be able to dismantle the theology of each religion which has tended to be displayed exclusively and dogmatically. A theology which usually only claims that only religion can build worldly welfare and usher in humans in God's heaven. The doors and rooms of heaven are only one that cannot be opened and entered except with the religion that he embraces. Even though such aology, we must admit, is something that is very worrying and can disturb the harmony of the people of religions in the present pluralistic era. An era in which all societies with all their elements are required to be interdependent and collect their fate together in order to create lasting peace. Here lies the challenge for religion (including Islam) to re-define itself in the midst of other religions. Or by borrowing the language John Lyden, an expert on religions, is